Chemical composition and antibacterial activity of the peel essential oils extracted from citrus fruits - Rudwan Badr Al-Deen; Bassam Aloklah; Lina Al-Amir (Future Science, 2021)
Citrus peel is an important source of essential oils (EOs). However, these EOs are not invested, although the annual production of citrus is high in Syria. The current study aimed to investigate chemical composition and antibacterial activity of some citrus peel EOs, namely: lemon (Citrus limon), orange (C. sinensis), grapefruit (C. paradisi), mandarin (C. reticulata) and bitter orange (C. aurantium). Gas chromatography–mass spectrometry (GC/MS) (gas chromatograph type: Agilent 7890A, auto sampler type: Agilent 7683B coupled to mass spectrometer, type Agilent 5975C, using DB–1 capillary column. EOs. concentration 1: 10 v/v in chloroform, injection volume 1 µl, split ratio 1: 80), was used to identify the chemical composition of the EOs, which were extracted by hydrodistillation technique, and chemical composition was expressed as Mean ± SD of three replications using SPSS V17 software. Minimal bactericidal concentration (MBC) was used to determine the antibacterial activity against five Gram-positive bacteria (Bacillus cereus, B. licheniformis, Staphylococcus haemolyticus, S. lugdunensis, Enterococcus faecalis) and five Gram negative bacteria (Klebsiella oxytoca, Citrobacter koseri, Serratia liquefaciens, Pseudomonas fluorescens and P. luteola). Limonene formed the vast majority of EOs (between 62.16 and 95.26% in lemon and orange EOs, respectively), but there were other active components, such as α–Pinene and β–Pinene. Lemon EO was the most effective one, with MBC values ranged between 4 μl.ml–1 (against Bacillus cereus) and 50 μl.ml–1 (against Serratia liquefaciens). Pseudomonas luteola (a Gram-negative bacterium) was the most sensitive species to citrus EOs (MBC values ranged between 4 and 50 μl.ml–1 for lemon and orange EOs, respectively); while S. liquefaciens (a Gram-negative bacterium) was the most resistant bacterium (MBC values were 50 and 150 μl.ml–1 for lemon and mandarin EOs, respectively) among all species studied in the current research.